Trend Rooftop Restaurant And Bar Sebagai Daya Tarik Wisata Kuliner di DKI Jakarta - Cindy Larini; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
In the middle of the city is really hard to find a touristattraction based on nature because usually the city is full of buildings. However, it is not impossible to build a touristattraction in a city. Nowadays, there are many buildings that being used as touristattraction based on rooftop restaurant andbar. This phenomenon is not only happened in Indonesia, but also becoming urban tourism trend in theworld. The data for this observation is collected by doing an observation, in-depth interview with the informants, and researching on archive collectionsabout rooftop restaurant andbar. The informants were determined based on purposive sampling, where the informants were selected based on certain specification. The informants of this observation are The Cloud Lounge & Dining Jakarta’smanager, SKYE Bar & Restaurant’smanager, and Henshin’ssupervisor. The result of this observation are touristattraction in those rooftop restaurants andbars, and the development on each of the rooftop restaurantsandbarsevery years. The development on rooftop restaurant andbar were analyzed by using fishbone analysis to see the impact of the changes on each rooftop restaurantsandbars. Key words: Urban Tourism, TouristAttraction, Rooftop Restaurant andBar, Fishbone Analysis.